Past-Year Nonmedical Use of Prescription Drugs among Women on Probation and Parole: A Cross-Sectional Study. Issue 3 (July 2018) - Hall, Martin T.; Ball, Diana; Sears, Jeanelle; Higgins, George E.; Logan, T K; Golder, Seana
Background: Prescription drug–related overdose deaths have increased dramatically in recent years. Women in the justice system experience high rates of drug use, victimization, trauma symptoms, and other health problems and would appear to be at high risk for nonmedical use of prescription drugs (NMUPD). This study will be among the first to describe prevalence and correlates of NMUPD among this population. Methods: This cross-sectional study collected data from 406 victimized women on probation and parole between 2010 and 2012. In a multiple logistic regression model, we differentiated women who reported past-year NMUPD from those who did not using demographic, health, other drug use, substance use treatment, and trauma symptom severity variables. Results: Past-year NMUPD was reported by 26.8% ( n = 109) of the overall sample. Women reporting NMUPD were significantly younger and more likely to be white. Past-year use of alcohol (adjusted odds ratio [AOR]: 3.3; 95% confidence interval [CI]: 1.8–6.1), marijuana (AOR: 3.6; 95% CI: 1.8–7.0), methamphetamines (AOR: 6.1; 95% CI: 1.7–21.3), and heroin (AOR: 8.4; 95% CI: 2.0–35.2) were significantly associated with NMUPD. Additionally, each unit increase in the measure assessing bodily pain was associated with a 40% increase (AOR: 1.4; 95% CI: 1.1–1.7) in the odds of NMUPD. Finally, meeting diagnostic criteria for posttraumatic stress disorder almost doubled (AOR: 1.9; 95% CI: 1.1–3.4) the odds of reporting past-year NMUPD. Conclusions: Victimized women on probation and parole report high rates of NMUPD, and this behavior intersects with other complex social, behavioral, psychological, and physical needs. The authors recommend increased access to trauma-informed correctional care among women in the justice system.